Persepsi Pengunjung terhadap Benteng Speelwijk sebagai Urban Heritage Tourism - Azzahra, Rafanisa Intan; Kusuma, Hanson Endra (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 11 No 2 (2024): October 2024DO - 10.24843/JRS.2024.v11.i02.p01, 2024)
Speelwijk Fort is one of the most visited historical heritage sites. Each visitor has their views in regard to this Fort. This study categorizes perception as a determining element in conservation activities. While no research has been conducted on this subject, this study explores visitors’ perceptions of Speelwijk Fort as an urban heritage tourist destination. It is designed to contribute towards developing an appropriate framework for managing, developing, and improving facilities, services, and quality provided by a historical tourism site. This study implements a grounded theory approach and is supported by an explorative qualitative method. Data collection was carried out using Google Maps review. Incoming reviews are selected based on a purposive sampling technique whose three main selection criteria are: reviews contain visitors’ evaluations that are relevant to the Speelwijk Fort; they are part of the 50 newest reviews representing the most updated conditions of the Speelwijk Fort; and review forms are completed with proper ratings. Using a three-stage content analysis method, this research reveals two groups of visitors’ perceptions. First are those who have positive perceptions and appreciate historical values, attractions, comfort, management, facilities, infrastructures, and the crowds offered by Speelwijk Fort during their visits. Second, visitors with negative perceptions experience discomfort and dissatisfaction with the management and facilities available at the fort. Keywords: Speelwijk Fort; visitor perceptions; urban heritage tourism; content analysis Abstrak Benteng Speelwijk menjadi salah satu situs peninggalan bersejarah yang ramai dikunjungi. Setiap pengunjung memiliki pandangannya sendiri akan benteng ini. Studi ini mengkategorikan persepsi sebagai elemen penting dalam kegiatan pelestarian. Ketika belum adanya penelitian tentang hal ini, studi ini mengeksplorasi persepsi pengunjung terhadap Benteng Speelwijk sebuah destinasi wisata kota tua. Studi didesain untuk memberi kontribusi dalam pembangunan kerangka yang tepat untuk pengelolaan, pengembangan, dan pembenahan fasilitas, pelayanan serta kualitas tempat pariwisata bersejarah. Penelitian ini menerapkan pendekatan grounded theory dan didukung oleh metode kualitatif yang bersifat eksploratif. Pengumpulan data dilakukan melalui Google Maps review. Review-review yang masuk diseleksi dengan teknik purposive sampling , dengan tiga kriteria utama, yaitu: review berisi evaluasi pengguna yang relevan dengan Benteng Speelwijk; merupakan 50 review terbaru yang mewakili kondisi terkini Benteng Speelwijk; dan review dilengkapi dengan rating. Dengan memakai tiga tahap analisis data isi (content analysis) sebagai metode analisisnya, penelitian ini mengungkap dua grup persepsi pengunjung. Pertama adalah kelompok pengunjung yang memiliki persepsi positif dan mengapresiasi nilai sejarah, daya tarik,  kenyamanan, pengelolaan, fasilitas, prasarana, serta menikmati keramaian yang ditawarkan oleh Benteng Speelwijk. Kedua, pengunjung yang memiliki persepsi negatif yang mengalami ketidaknyamanan dan ketidakpuasan terhadap pengelolaan dan fasilitas yang tersedia di benteng ini. Kata kunci: Benteng Speelwijk; persepsi pengunjung; urban heritage tourism ; analisis isi